Difusi Inovasi dalam Program Sekolah Keluarga : Pengalaman dari Kota Bukittinggi - Chairunnisa Chairunnisa; Siska Sasmita (Universitas Sebelas Maret, 2022)
‘Sekolah Keluarga’ (Family School) is a program initiated by the Bukittinggi City Empowerment and Family Welfare Mobilization Team (TP PKK), as an effort to overcome the decline in the quality of families in Bukittinggi City. This program was first implemented in 2018 by targeting families in villages with high social problems. The City Government (Pemko) of Bukittinggi claims that this program is different from conventional school activities or other social problem alleviation efforts in terms of infrastructure, curriculum, and output. Qualitative method with a descriptive approach to examine whether the new program initiated by the Pemko Bukittinggi can be categorized as an innovation. For this reason, the authors interviewed the parties involved in the Family School Program, namely: technical implementers, technical implementing assistants, a team of presenters and participants, in addition to making direct observations of Family School activities and studying documents related to this program. The analysis of the findings shows that the Family School Program initiated by the Pemko Bukittinggi is categorized as an incremental innovation. This program is in line with most of the innovation attributes proposed by Everett M. Rogers. namely relative advantage, complexity, trialability, and observability. However, it does not meet the compatibility indicator because its existence does not replace the previous program. This program should be maintained so that later it can become a solution to overcome social problems that are happening.